The Role of Applied Linguistics in Language Attrition at a Bilingual School - Laba, I Nengah; Ni Putu Nia Krisna Dewi; Raisya Syahma Aqila (Center of Language and Cultural Studies [CLCS], 2024)
This paper examines the role of applied linguistics of language attrition in bilingual school. It explores the field of applied linguistics, with a particular emphasis on the role of language attrition in bilingual educational environments. This study discusses the theoretical foundations of applied linguistics and language attrition. Qualitative descriptive method is used to analyze the data. The result of this study shows that applied linguistics has an important role to solving the problems caused by language attrition. The research, grounded in theoretical frameworks such as Applied Linguistics, Language Attrition, the Matrix Language Frame (MLF) Hypothesis, and Sociolinguistic Perspective, provides a comprehensive understanding of the underlying mechanisms of language attrition. The significance of applied linguistics in addressing language attrition is emphasized by the study. It offers research methods, theoretical underpinnings, and useful tactics for language preservation and improvement. Community-based initiatives, educational interventions, and language assessment all benefit from applied linguistics. Additionally, it draws attention to the useful ramifications of language attrition in bilingual education and provides strategies for successful interventions that preserve linguistic diversity.